Longitudinal Invariance Analysis of the Short Grit Scale in Chinese Young Adults - Luo, Jie; Wang, Meng-Cheng; Ge, Ying; Chen, Wei; Xu, Shuang (Frontiers in Psychology, 2020)
The current study examined the longitudinal measurement invariance (LMI) of the Short Grit Scale (Grit-S) in a survey sample of Chinese young adults (N = 233, 48.9% male, mean age = 19.36 years, SD = 0.90 years) who completed the Grit-S twice over a 3-month interval. Confirmatory factor analysis was conducted to examine the LMI of the Grit-S across time. Results showed that the Grit-S has strict longitudinal invariance (i.e., equality of factor patterns, factor loadings, item intercepts, and item uniqueness for all items) over time. Additionally, the internal consistency indices of the Grit-S were acceptable across time, the stability coefficients over time were moderate, and latent factor means did not differ significantly across time. In sum, these findings suggest that the Grit-S has satisfactory longitudinal properties when used in Chinese young adults.